Конституциялық құқық пен парламенттік құқық ара қатынасындағы ерекшеліктер - Сəтбаева, Қ. (ҚарМУ басп., 2010)
В данной статье рассматриваются понятие, предмет и источники парламентского права, которое определяется как подотрасль конституционного права и рассматривается в системе конституционного права. Автор показывает соотношение конституционного и парламентского права. In the given article are considered notion, subject and source of parliamentary law. Parliamentary law is defined as branch of constitutional law and considered in system of constitutional law. In given article the concept, a subject and sources of the parliamentary right are considered. The parliamentary right is defined as part of constitutional law and considered in constitutional law system.
Keywords: парламенттік құқық; конституциялық құқық; заң; заңнама; құқықтану; ұғым; парламентаризм; құқықтық норма; Қазақстан Республикасы